Technical Efficiency and Input Utilization in Lowland Rice Farming in Tanjung Lapang Village North Kalimantan Indonesia - Banyuriatiga Banyuriatiga; Anang Sulistyo; Khaerunnisa Khaerunnisa; Suryaningsih Suryaningsih (Buletin Penelitian Sosial Ekonomi Pertanian Fakultas Pertanian Universitas Haluoleo, 2025)
This research seeks to outline the profile of farmers in Tanjung Lapang Village, determine the factors that shape the technical efficiency of rice farming, and assess the level of technical efficiency in rice cultivation (Oryza sativa L.) within the village in West Malinau District. The study is needed to measure the efficiency of input utilization and to determine the variables that shape productivity outcomes. This study focuses on examining the production factors involved in rice paddy farming and evaluating the technical effectiveness of the cultivation process. The study was conducted in the West Malinau subdistrict from January to February 2024. The method used was probability sampling, with 50 farmers selected as respondents. Information was obtained through interviews, observations, and recorded images, with questionnaires as the main instrument. The dataset was analyzed using descriptive methods, multivariate regression, and a production elasticity approach to determine how each input influences agricultural output. The results indicate that land size and chemical nutrient use are the most decisive factors in shaping rice production. In contrast, the combined contributions of land, seeds, chemical nutrients, Plant protection chemicals, and human resources account for 47.6% of yield variation, with the remainder influenced by external factors such as weather, soil conditions, water availability, and technology adoption. The elasticity value below one reflects diminishing proportional returns, where additional inputs yield increasingly smaller output gains. These findings provide a strategic basis for guiding farmers to optimize resource allocation and adopt targeted interventions, such as balanced chemical fertilization, improved cultivation practices, and better land and pest management, to enhance sustainable productivity.